PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF MATA KULIAH PERAWATAN KULIT WAJAH - Murni Astuti; Rahmiati Rahmiati; Sri Zulfia Novita; Rahmi Oktarina (Universitas Negeri Padang, 2019)
Learning Skin Care is one of the compulsory subjects in the Department of Beauty And Cosmetology FPP UNP. The problems encountered in learning Facial Skin Care are students having difficulty in understanding massage tehnic and problematic facial care techniques with technology. This causes student learning outcomes are relatively low. The purpose of this research is to develop interactive multimedia learning media on Facial Skin Care courses that are practical, valid and effective. This research was conducted in the cosmetology and beauty department of FPP UNP. This research uses the Research and Development (R&D) research method. Interactive multimedia validation of Facial Skin Care courses conducted by material validators and media and language display an average of 3.68% with the category